Why optimisation of a system of systems is both unattainable and unnecessary. (1st January 2012) - Hester, Patrick T.
The operational and managerial independence, geographic distribution, emergent behaviour, and evolutionary development that characterise a system of systems (SoS) also ensure that it is impossible to truly optimise it. However, using the concept of satisficing, we can declare that a 'good enough' solution is in fact, sufficient. Why are we all right with this potentially unsettling notion in the context of a system of systems? In part, due to the principle of finite causality introduced in this paper, stating no system outcome can have infinitely bad (or good) implications; thus, the outcome of any action or series of actions is finite in nature. This realisation further bolsters the acceptability of an inherently sub-optimal SoS. This paper explores the notions of why optimisation of a SoS is both: 1) unattainable based on its inherent characteristics and associated systems principles; and 2) unnecessary in practice.